Le quatre-vingtième anniversaire de la Société de géographie de Québec - Camu, Pierre (Cahiers de géographie du Québec, 1957)
The Québec Geographical Society dates back to 1877 and is celebrating this year its 80 th anniversary. This Presidential address was read on the occasion of a special meeting of members and guests of the Society on November, 14 th, 1957. The President reviews briefly the history of the Society : its past members, its publications and its various activities, lectures, field work, field trips, film presentations, etc. The President pays tribute to the Québec Provincial Government which bas given the Society an annual grant for many years, and to Laval University who bas sheltered the Society for more than seventy years.